Status of Water Supply and Sanitation in Hadejia Local Government, Jigawa State, Nigeria (London Journal of Research In Humanities and Social Sciences, 2023)
This research dwells on status of water supply and sanitation in the study area. It employs both primary and secondary data. Primary data were collected using questionnaire as tools for data collection where multistage sampling was adopted. The study area was stratified and questionnaire administered systematically to solicit information from respondents. The research established strong relationship between economic status, level of education, water supply and environmental sanitation. The water supply is frequent and majority about 79% source it form tap water system and have toilet in their houses. The distance to the water sources is very short, majority trek less than 500 metres (78%). The overall status of water supply and sanitation in Hadejia is good.
Keywords: Nigeria; Water supply; Sanitation; Hadejia; Jigawa